COVID Feel Good—An Easy Self-Help Virtual Reality Protocol to Overcome the Psychological Burden of Coronavirus - Riva, Giuseppe; Bernardelli, Luca; Browning, Matthew H. E. M.; Castelnuovo, Gianluca; Cavedoni, Silvia; Chirico, Alice; Cipresso, Pietro; de Paula, Dirce Maria Bengel; Di Lernia, Daniele; Fernández-Álvarez, Javier; Figueras-Puigderrajols, Natàlia; Fuji, Kei; et al. (Frontiers in Psychiatry, 2020)
Background: Living in the time of the COVID-19 means experiencing not only a global health emergency but also extreme psychological stress with potential emotional side effects. Crucially, lockdown and confinement measures isolate people who become the first and the only ones in charge of their mental health. Aims: This pragmatic trial aims to provide the evidence that a weekly self-help virtual reality (VR) protocol can help overcome the psychological burden of the Coronavirus by relieving anxiety, improving well-being and reinforcing social connectedness. The protocol will be based on the “Secret Garden” 360 VR video online (www.covidfeelgood.com) which simulates a natural environment aiming to promote relaxation and self-reflection. 360 or spherical videos allow the user to control the viewing direction. In this way, the user can explore the content from any angle like a panorama and experience presence and immersion. The “Secret Garden” video is combined with daily exercises that are designed to be experienced with another person (not necessarily physically together), to facilitate a process of critical examination and eventual revision of core assumptions and beliefs related to personal identity, relationships and goals. Methods: This is a multicentric, pragmatic pilot randomized controlled trial involving individuals who experienced the COVID-19 pandemic and underwent a lockdown and quarantine procedures. The trial is approved by the Ethics Committee of the Istituto Auxologico Italiano. Each research group in all the involved countries aims at enrolling at least 30 individuals in the experimental group experiencing the self-help protocol, and 30 in the control group, over a period of 3 months to verify the feasibility of the intervention. Conclusion: The goal of this protocol is for VR to become the “surgical mask” of mental health treatment. Although surgical masks do not provide the wearer with a reliable level of protection against the coronavirus compared with FFP2 or FFP3 masks, surgical masks are very effective in protecting others from the wearer’s respiratory emissions. The goal of the VR protocol is the same: not necessarily to solve complex mental health problems but rather to improve well-being and preserve social connectedness by using the beneficial effects of positive emotions..